Growth and biomass of Vallisneria giganteas leaf in Senggarang River flow, Tanjungpinang City, Riau Islands - Nengsih, Listia; Apriadi, Tri; Muzammil, Wahyu (Acta Aquatica: Aquatic Sciences Journal, 2021)
The objective of this study were to determine the density, the growth rate, and growth of biomass of Vallisneria gigantea. This research was conducted on May-June 2020 in a river in Senggarang, Tanjungpinang City. This research was used random sampling method of 30 points using transect quadrant (50x50 cm). The results showed that V. gigantea had a density value of 148.80 ind/m2. The growth rate of V. gigantea was 0.06 cm/day and biomass growth were 21.71 gr/m2. Light intencity was the principle component of V. giganteas leaf growth rate while  pH, velocity, and temperatur were principle component for growth biomass leaf.Keywords: Density; Giant Vallisneria; Growth; Macrophyte; Productivity